To Find the Optimum Results for Enhancing the Properties of Carbon Nanotubes - Singh, Damanpreet (My University, 2012)
This research is based on the link between molecular mechanics theory and solid mechanics theory through an analytical approach, investigating for the young’s modulus of single-walled carbon nanotubes (SWCNT). The influence of diameter and chirality on the Young’s modulus of SWCNT is also investigated. A SWCNT is considering as a continuumshell model which is composed of the discrete molecular structures linked by the carbon-tocarbon bonds. The young’s modulus is investigated for the SWCNT (both zig-zag and armchair) considering various parameters affecting it, in terms of the chiral indices (n, m). Based on the presented theory, it has been predicted that the optimum values of young’s modulus for zig-zag lies in the range of (0.6346–1.0460 TPa) and for armchair, it lies in the range of (.5247–.9352 TPa). Also by varying the thickness of the SWCNT as 0.66 Å, the obtained values for the young’s modulus lies in the range of (2.6734–.4027 TPa) for zig-zag. And for armchair, it lies in the range of (1.7504–.2366 TPa) respectively. Also, the effect of increasing temperature is investigated on the extreme points of nanotube’s bond length. The theoretical prediction on elastic properties agreed reasonably with other existing experiment and theoretical results. The present formulas are able to serve as a good approximation of the young’s modulus for SWCNTs.
Master of Engineering (Production and Industrial Engineering)
Keywords: CNT; force constant; young's modulus